Non-alcoholic fatty liver disease combined with rheumatoid arthritis exacerbates liver fibrosis by stimulating co-localization of PTRF and TLR4 in rats - Zhang, Shengpeng; Zhu, Peng; Yuan, Jianan; Cheng, Kunming; Xu, Qixiang; Chen, Wei; Pan, Zui; Zheng, Yongqiu (Frontiers in Pharmacology, 2023)
Rheumatoid arthritis (RA) has a high prevalence in patients with non-alcoholic fatty liver disease (NAFLD); however, the underlying mechanism is unclear. To address this, our study established a rat model with both NAFLD and RA by feeding a high-fat diet (HFD) and administering intradermal injection of Freund’s complete adjuvant (FCA) with bovine type II collagen. Collagen-induced RA (CIA) was confirmed by hind paw swelling and histological examination. The histomorphological characteristics of NAFLD were evaluated by Masson’s trichrome and hematoxylin-eosin staining. The development of NAFLD was further evaluated by measuring serum concentrations of triglyceride (TG), total cholesterol (T-CHO), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lipopolysaccharide (LPS). The results showed that HFD feeding exacerbated secondary inflammation in CIA rats, whereas FCA/bovine type II collagen injection increased serum levels of ALT, AST, TG, T-CHO, and LPS and exacerbated hepatic fibrosis in both normal and NAFLD rats. Interestingly, NAFLD + CIA significantly promoted the expression of PTRF, a caveolae structure protein involved in hepatic lipid metabolism and affecting downstream signaling of Toll-like receptor 4 (TLR4) and PI3K/Akt activation. High resolution confocal microscopy revealed increased PTRF and TLR4 co-localization in hepatic small vessels of NAFLD + CIA rats. AAV9-mediated PTRF knockdown inhibited TLR4 signaling and alleviated hepatic fibrosis in NAFLD + CIA rats. Together, these findings indicate that NAFLD combined with CIA causes synovial injury and enhances non-alcoholic fatty liver fibrosis in rats. PTRF could attenuate the symptoms of NAFLD + CIA likely by affecting TLR4/PTRF co-expression and downstream signaling.